Analisis Akuntabilitas Lembaga Filantropi Islam di Aceh (Studi Pada Baitul Mal Provinsi Aceh): Studi pada Baitul Mal Provinsi Aceh - Adnan, Muhammad Ichsan; Makraja, Fahmi; Azhari, Rizka; Farhana, Intan (ITB AAS INDONESIA Surakarta, 2026)
This study aims to analyze online accountability disclosure through a model developed based on the perspective of maqashid shariah. The research was conducted at Baitul Mal of Aceh Province as a public fund management institution administering Zakat, Infaq, Sadaqah (ZIS), and waqf. The study employs a quantitative approach using content analysis of information presented on the institution’s official website. The findings indicate that Baitul Mal of Aceh Province has achieved a high level of accountability disclosure in the dimensions of safeguarding the human self (83.33%) and preserving the value of human life (82.61%). Meanwhile, the dimensions of safeguarding society and protecting the physical environment each demonstrate an achievement level of 75.00%. These results suggest that the utilization of online media has relatively comprehensively supported the fulfillment of accountability based on maqashid syariah, although there remains room for strengthening the social and environmental dimensions. This study contributes to the development of the literature on online accountability within the context of Islamic philanthropy and offers practical recommendations for optimizing digital strategies in the accountability practices of public Islamic fund management institutions.